Successful Pregnancy Outcome with High dose Heparin Therapy in Antiphospholipid Antibody Syndrome - Ranjith, MP; Divya, Ranjith; Meera, S; Bahuleyan, Shabu; Kuryan, Roney Joseph (Journal of Medicine, 2010)
Antiphospholipid antibody syndrome is an autoimmune disease characterized by thrombosis, both arterial and venous, recurrent spontaneous abortion and the persistence of positive antiphospholipid antibodies. Placental thrombosis is believed to be the cause of recurrent abortions, characteristic of the syndrome. We report a pregnant with antiphospholipid antibody syndrome patient with history of recurrent miscarriages and managed successfully with high dose heparin. Keywords: Antiphospholipid antibody syndrome; recurrent intra uterine death; Heparin DOI: 10.3329/jom.v11i2.5476 J MEDICINE 2010; 11 : 205-206